DISTINCTIVE FEATURES OF DIAGNOSTICS, TREATMENT AND PREVENTIVE MEASURES OF PATHOLOGICAL SCARS OF MALLIOFACIAL AREA - V.V. Nahaychuk; L.I. Shkilniuk (Український стоматологічний альманах)
Health and beauty of human skin in the modern world is one of the main features of attractiveness of both women and men. Skin is the largest organ of the human body, depending on the age, height and weight its area is from 1.7 to 2.6 m2, and weight is about 16% of the total body weight. As a reflection of internal human